2022
DOI: 10.1177/13623613221135818
|View full text |Cite
|
Sign up to set email alerts
|

Looking through rainbow-rimmed glasses: Taking neurodiversity perspective is related to subjective well-being of autistic adults

Abstract: Finding new ways of supporting the well-being of autistic adults is an essential goal for research and practice. We tested the predictive value of attitudes towards autism (as neurodiversity or as a disorder) and identification with other autistic people, on the psychological distress and self-esteem of autistic adults ( n = 109). Adopting a neurodiversity attitude not only predicted higher self-esteem but also served as a protective factor against the negative impact of identification with other autistic peop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 76 publications
2
13
0
Order By: Relevance
“…Our findings also highlighted that autism provided ‘a framework to understand myself better’ and provided a lens through which to review past experiences and come to a level of self-acceptance. This fits with previous research showing a relationship between autistic identity and mental health, 4,81 83 and the importance of diagnosis. 84 Our research also outlined the impact of positive interpersonal relationships with other autistic people and access to autistic community.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings also highlighted that autism provided ‘a framework to understand myself better’ and provided a lens through which to review past experiences and come to a level of self-acceptance. This fits with previous research showing a relationship between autistic identity and mental health, 4,81 83 and the importance of diagnosis. 84 Our research also outlined the impact of positive interpersonal relationships with other autistic people and access to autistic community.…”
Section: Discussionsupporting
confidence: 92%
“…Autism pride, perceived benefits of autism, dissatisfaction with being Autistic, and helplessness associated with being Autistic were all significant individual predictors of personal self‐esteem (Corden et al, 2021; Nguyen et al, 2020). Other studies also found that higher collective self‐esteem was associated with stronger Autistic social identification (Cooper et al, 2017, 2021) and that self‐definition (i.e., feeling the same as other Autistic people) was a significant individual predictor of global self‐esteem (Ferenc et al, 2023).…”
Section: Resultsmentioning
confidence: 88%
“… Cooper et al (2017) and Ferenc et al (2023) only reported n (%) for female participants. As such, all other participants ( n = 170) are represented in the “other gender identities” category. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations